Effects of postbiotic and inulin supplements on growth performance, gut morphology, gene expression and fecal characteristics of broiler chicken - Karrem, Karwan Yaseen (2016)
Antibiotic growth promoters (AGP) are effective in modulating the gut microflora and promoting growth performance in birds. Nonetheless, prolonged use of AGP can cause antibiotic resistance and residual effects, which could imperil the health of birds and human consumers. Prebiotics, probiotics and their combinations are potent replacements for AGP. Nonetheless, commercial probiotics have consistently failed to meet the anticipated capability and their efficacy is uncertain. In addition, the use of probiotics could lead to the occurrence of antibiotics gene resistance that could be transferred between organisms. This justifies the need to search for suitable and safe alternative to probiotics. Postbiotic, a metabolite of probiotics exhibits probiotic effect without living cells. Despite the efficacies of postbiotics and prebiotics, the synergistic effects of prebiotic and postbiotic combinations have not been elucidated. This study examined the influence of postbiotic produced by strains of Lactobacillus plantarum, and inulin combinations on growth performance, gut morphology, meat quality, gene expression and fecal characteristics of broiler chickens. The study was partitioned into three experiments. The first experiment examined the inhibitory activity of postbiotic produced by strains of Lactobacillus plantarum using reconstituted media supplemented with inulin. Postbiotics were produced by six strains of L. plantarum (RG11, RG14, RI11, UL4, TL1 and RS5) using reconstituted media supplemented with different levels of inulin (0, 0.2, 0.4, 0.6, 0.8, and 1.0) yielding 36 combinations. The modified inhibitory activity (MAU) of the produced postbiotics were tested against indicator microorganism, Pediococcus acidilactici and pathogenic microorganisms; Listeria monocytogenes, Salmonella enterica, Vancomycin-Resistant Enterococci (VRE) and Escherichia coli. The combination of postbiotic and inulin had higher (P< 0.05) MAU than postbiotic alone against all indicator organisms except P. acidilactici, and E. coli. The RI11 + 0.8% Inulin, RG14 + 0.8% Inulin and RG14 + 0% Inulin had significantly (P< 0.05) higher MAU/mL against P. acidilactici than other treatments. The RI11 + 0.8% Inulin and RG14 + 0.4% Inulin had a significantly (P< 0.05) higher MAU/mL against VRE. The MAU/mL against L. monocytogenes was greater in RI11 + 1.0% Inulin, RI11 + 0.6% Inulin and RI11 + 0.8% Inulin. The combinations of RS5 + 1.0% Inulin, RS5 + 0.8% Inulin and RS5 + 0.6% Inulin had greater MAU/mL against S. enterica; whereas in E. coli, the inhibitory activity had higher activity that can only be found in RS5 + 0.8% Inulin. The combination of postbiotics and inulin had higher optical density and lower pH, which corresponds to increased inhibitory activity against indicator organisms. The results of this study showed that postbiotics and inulin combinations inhibit the proliferation of pathogenic bacteria. Four combinations of postbiotic and inulin with the highest MAU were used as a feed additive in the second experiment. The second experiment examined the influence of postbiotics on growth performance, apparent ileal digestibility (AID), meat quality and gene expression in broiler chickens. A total of 280, one day-old male, Cobb broiler chicks were randomly assigned to 8 treatment groups. The treatments include; basal diet (negative control), basal diet+ neomycin and oxytetracycline (positive control), (T1) basal diet+0.3% postbiotic RI11, (T2) basal diet+0.3% postbiotic RG14, (T3) basal diet+0.3% postbiotic RI11+0.8% inulin, (T4) basal diet+0.3% postbiotic RI11+1.0% inulin, (T5) basal diet+0.3% postbiotic RG14+0.8% inulin, and (T6) basal diet+0.3% postbiotic RG14+1.0% inulin. Birds fed postbiotic and inulin combinations had greater (P< 0.05) final body weight, body weight gain and feed efficiency compared with the control birds. Similarly, supplementation of postbiotic and inulin combinations increased (P< 0.05) the population of faecal lactic acid bacteria and villi height of small intestine and lowered faecal Enterobacteriaceae. Birds fed postbiotics and inulin combinations had lower (P< 0.05) drip loss and higher (P< 0.05) lightness of Pectoralis major muscle compared with the control birds. Birds fed diets supplemented with postbiotic and inulin combinations had greater (P<0.05) percentage of tibia bone Ca and P, faecal acetic acid, propionic acid and total organic acid compared with the control birds. The liver of birds fed T4 and T6 had higher Insulin-like growth factor 1 (IGF-I) expression compared with other treatments while T6 had higher growth hormone receptor (GHR) mRNA expression compared with other treatments. The supplementation of postbiotics and inulin combination had beneficial effect on total body weight, feed efficiency, mucosal architecture, and expression of IGF-I and GHR mRNA in broiler chickens. The third experiment examined the effect of graded levels of RG14 and 1% inulin on growth performance, meat quality and gene expression in broiler chickens. A total of 216, one day old male Cobb chicks were randomly assigned to six dietary treatments. The treatment were basal diet (negative control), basal diet+ neomycin and oxytetracycline (positive control), (T1) basal diet+0.15% postbiotic RG14+1.0% inulin (T2) basal diet+0.3% postbiotic RG14+1.0% inulin (T3) basal diet+0.45% postbiotic RG14+1.0% inulin, (T4) basal diet+0.6% postbiotic RG14+1.0% inulin. Supplementation of 0.15 and 0.45 % RG14 with 1% inulin improved final body weight, weight gain and meat quality of broiler chickens compared with other treatments. The supplementation of postbiotic and inulin combinations increased the concentration of acetic acid, ileal cytokine expression, plasma immunoglobulin IgG and IgM, and population of total bacteria and beneficial bacteria and reduced the population of Enterobacteria and E. coli compared with the control diet. The combination of 0.15% RG14 with 1% inulin is potential replacement for antibiotic growth promoter (AGP) in the poultry industry.